AB0848 Rituximab treatment for spondyloarthritis. A nationwide series: Data from the air registry. (23rd January 2014) - Wendling, D.; Dougados, M.; Berenbaum, F.; Brocq, O.; Schaeverbeke, T.; Mazieres, B.; Marcelli, C.; Le Parc, J.-M.; Bertin, P.; Robin, M.; Sibilia, J.; Lafforgue, P.; et al.
Abstract : Background: Only few data are available about rituximab (RTX) in spondyloarthritis. Objectives: The aim of this study was to evaluate efficacy and safety of rituximab treatment in several subsets of spondyloarthritis (SpA) using the data of the AIR (AutoImmunity and Rituximab) registry. Methods: All patients receiving rituximab (RTX) for spondyloarthritis, and included in the AIR registry from September 2005 to September 2010, were eligible for the study, and retrospectively analysed. Patient characteristics, indications, therapy regimen, and tolerance and efficacy of RTX were collected at baseline and at 3- and 6-month follow-up, then every 6 months or at disease relapse. The response to treatment was evaluated by BASDAI reduction over 2 units (on a 0-10 scale) for axial disease, joint count reduction over 20% for peripheral disease, and CRP reduction. Side effects were recorded. Results: Among the 595 patients included in the AIR registry, 26 SpA patients, from 13 centres were reported; mean age 51 years, 13 men, ankylosing spondylitis (10), undiffenciated spondyloarthritis (7), and psoriatic arthritis (9). The mean disease duration was 8.8 years (1-40), extra articular features: psoriasis 12 cases, uveitis 4 cases, Crohn's disease 3 cases. The mean number of DMARDs before rituximab was 2.4, a previous TNF blocker has been used in 23 cases; rituximab treatment courses was a mean of 1.5 (1 to 5), with a mean follow up of 17.8 months, and a total of 35.6 patients-years. Efficacy was evaluable in 23 cases, with a response between 3 to 7 months after treatment in 11 cases: 3 out of 3 anti-TNF naïve patients and 8 out of 20 anti-TNF non responder patients. No differences were seen between responders and non responders for baseline CRP, HLA-B27 presence, gender, disease duration, extra articular features, immunoglobulin serum levels, clinical presentation (axial/peripheric) or initial diagnosis (AS, PsA, SpA). Safety: one severe infection, one cardiac failure, 2 cases of psoriasis deterioration, 2 uveitis episodes (one de novo) were recorded. Conclusions: In this nationwide open experience of rituximab on several subsets of spondyloarthritis, we saw only a moderate efficacy, more evident for patients naive for anti TNF agents. Disclosure of Interest: None Declared